Evaluation of the translocation of soil metals and waste for lettuce, arugula and radish: case study Mariana-Minas Gerais-Brazil (Research, Society and Development, 2022)
Mineral exploration is a relevant economic activity developed in Brazil, mainly in the State of Minas Gerais. The Quadrilátero Ferrífero region is considered one of the largest polymineral provinces on the planet and has important reserves of iron ore, manganese, nickel, aluminum and gold. With the failure of the Fundão dam in Mariana-MG, in 2015, millions of tons of tailings overflowed, being deposited in the soil and water resources. The tailings load first reached the Santarém Dam, causing its overtopping, subsequently reaching the sub-district of Bento Rodrigues, Rio Gualaxo do Norte, Rio Carmo, Rio Doce and the Atlantic Ocean. There were 663.2 km of water bodies directly impacted, 41 municipalities and two states affected: Minas Gerais and Espírito Santo. Given the magnitude of the damage caused to the ecosystem and the lack of information and studies in the health area, this research aims to investigate the transfer of contamination of metals present in the tailings to the trophic chain, through the cultivation of food on the contaminated substrate. and chemical determinations in the shoot and root system. Evaluation of the Translocation Factor of the metals was developed in vegetables (lettuce, arugula and radish), cultivated with natural soil of Mariana-MG and with mining tailings. The results of the tests with vegetables indicate samples that presented a Translocation Factor greater than 1, showing the transport of metals from the roots to the aerial part of the vegetables, which can represent a risk to the health of the population.